The Secret Mistress - Balogh, Mary (London : Piatkus, 2011)
When Edward Ailsbury, the new Earl of Heyward, rescues Angeline Dudley from public embarrassment, Angeline falls instantly in love. But the stuffy Earl has little concern for Angeline. Edward wishes only to wed an old friend for an amicable companionship, a good match for his staid persona. But Angelina may show Edward that comfort is no match for passion.
Keywords: Mistresses -- Fiction; Romance fiction; Husband and wife -- Fiction; English fiction